Strategic Management in Improving the Performance of Madrasah Aliyah (MA) in Sukabumi District - Makhfudz Makhfudz; Hendi Suhendraya Muchtar; Deti Rostini; Heru Sujiarto (International Journal of Nusantara Islam, 2021)
This research is motivated by the condition of Madrasah Aliyah's performance is still weak in the management of education and learning. Weak performance is suspected to have not been implemented properly in strategic management at Madrasah Aliyah. The general objective of the study is to determine the performance improvement of Madrasah Aliyah in Sukabumi Regency through the application of strategic management and the specific objectives are to describe (1) Formulation, (2) Implementation, (3) Evaluation and control, (4) Results obtained, (5) Constraints that arise, and (6) Solutions to overcome obstacles that arise in the implementation of strategic management in improving the performance of Madrasah Aliyah. The grand theory used is Pearce and Robinson's strategic management theory. Using a qualitative approach, descriptive method with data collection techniques through interviews, observations, and documentation studies. The results of the study show that in general strategic management has improved the performance of Madrasah Aliyah, and specifically as follows: (1) The formulation of strategic management has been implemented through the formulation of the vision, mission, objectives, policies, and madrasa programs through limited meetings. The formulation has not gone through a special workshop with a comprehensive discussion, (2) The implementation of strategic management has been carried out. Educational management implements madrasah-based management (MBM) by developing two integrated programs, namely madrasa managerial programs and madrasa academic programs. The implementation of madrasa management follows government regulations and foundation policies, (3) Evaluation and control of strategic management through four activities, namely an assessment from the Ministry of Religion through Madrasah Supervisors, activities of the Internal Quality Assurance System (SPMI) through Madrasah Self Evaluation (EDM) as the basis for the preparation of e-mails. RKAM and External Quality Assurance System through Madrasah Accreditation, Assessment from Foundation Management, and assessment of public perception. There are no specific criteria for assessment from foundations and the community, (4) The results obtained from the implementation of strategic management are an increase in the quality of education governance and the learning process. The implementation of education is getting better. Madrasah personnel can carry out their duties and functions according to what has been set. Students excel in various competition activities, both academic and non-academic, (5) Constraints that arise include limited facilities and infrastructure, not all national education standards are implemented optimally, madrasas do not have full authority, the majority of teacher status are Non-PNS so that their welfare is relatively low. is still small, and education financing still relies on Central BOS funds and BPMU from the Province, and (6) Solutions, all obstacles are gradually overcome to minimize problems in performance. In conclusion, empirically strategic management has been applied and can improve the performance of Madrasah Aliyah Sukabumi Regency. Improvement in the implementation of education and learning. Private Aliyah Madrasas follow government regulations and policies set by the foundation.